Clinical relevance of partial HPV16/18 genotyping in stratifying HPV‐positive women attending routine cervical cancer screening: a population‐based cohort study. (12th January 2021) - Gori, S; Battagello, J; Gustinucci, D; Campari, C; Zorzi, M; Frayle, H; Passamonti, B; Sartori, G; Bulletti, S; Fodero, C; Cesarini, E; Faggiano, R; et al.
Abstract : Objective: To evaluate partial HPV16/18 genotyping as a possible biomarker to select women attending HPV‐based cervical cancer screening at higher risk to be referred to colposcopy. Design: Population‐based cohort study. Setting: Organised cervical cancer screening programmes (Italy). Population: Women with high‐risk HPV infection (period: 2015–2019). Methods: We analysed the association between partial HPV16/18 genotyping, cytology triage and histologically confirmed diagnosis of high‐grade cervical intraepithelial neoplasia (CIN3 + ) lesions. Main outcome measures: Detection rate (DR) and positive predictive value (PPV) for histologically confirmed CIN3 + (any episode in the 2 years after baseline); sensitivity for CIN3 + and number of colposcopies needed for lesion detection. Results: The study included 145 437 women screened with HPV testing by the clinically validated COBAS 4800 HPV assay (Roche). Overall, 9601 (6.6%) women were HPV + at baseline; HPV16 and HPV18 were present in 1865 and 594 samples, respectively. The cumulative (baseline plus 1‐year repeat) cytology positivity was 42.8% and high‐grade cytology was significantly higher ( P  < 0.0001) among women with HPV16 infection at baseline (15.2%). The cumulative CIN3 + DR for women with HPV16, HPV18 and other HPV‐type infections was 9.8%, 3.4% and 1.8%, respectively. Conclusions: Partial HPV16 genotyping may play a role in triage, whereas HPV18 seems to behave much more similarly to the other HPV types and does not provide additional stratification. HPV16 genotyping combined with high‐grade cytology can be envisaged as a triage biomarker in cervical screening to maximise CIN3 + detection while minimising colposcopy at baseline or 1‐year repeat. Tweetable abstract: HPV16 genotyping combined with high‐grade cytology can be used as triage biomarker for CIN3 + in HPV‐positive women. Tweetable abstract: HPV16 genotyping combined with high‐grade cytology can be used as a triage biomarker for CIN3 + in HPV‐positive women.